Neighbourhood greenspace and physical activity and sedentary behaviour among older adults with a recent diagnosis of type 2 diabetes: a prospective analysis. Issue 11 (14th November 2019) - Chong, Shanley; Mazumdar, Soumya; Ding, Ding; Morgan, Geoff; Comino, Elizabeth Jean; Bauman, Adrian; Jalaludin, Bin
Abstract : Objectives: Greenspace is one of the important factors that can promote an active lifestyle. Thus, greener surroundings may be a motivating factor for people with newly diagnosed diabetes to engage in more physical activity. Given that diagnosis of type 2 diabetes (T2D) may serve as a window opportunity for behavioural modification, we hypothesise that the association between neighbourhood greenspace and physical activity among people with newly diagnosed T2D may be greater than those not diagnosed with T2D. The aim of this study was to investigate the association between access to greenspace and changes in physical activity and sedentary behaviour, and whether these associations differed by T2D. Design: Prospective cohort. Setting: New South Wales, Australia. Methods: We used self-reported information from the New South Wales 45 and Up Study (baseline) and a follow-up study. Information on sitting, walking and moderate to vigorous physical activity was used as outcomes. The proportion of greenspace within 500 m, 1 km and 2 km road network buffers around participant's residential address was generated as a proxy measure for access to greenspace. The association between the access to greenspace and the outcomes were explored among the newly diagnosed T2D group and those without T2D. Results: Among New T2D, although no significant changes were found in the amount of walking with the percentage of greenspace, increasing trends were apparent. There was no significant association between the percentage of greenspace and changes in amount of moderate to vigorous physical activity (MVPA). Among No T2D, there were no significant associations between the amount of MVPA and walking, and percentage of greenspace. For changes in sitting time, there were no significant associations with percentage of greenspace regardless of buffer size. Conclusions: In this study, there was no association between access to greenspace at baseline and change in walking, MVPA and sitting time, regardless of T2D status.